Analysis of Compliance with the Use of Personal Protective Equipment (PPE) among Healthcare Workers in the Emergency Department of Lirik Primary Health Care Center - Risty Nanda Maisi Putri; M. Kamali Zaman; Said Mardani (JURNAL KESMAS DAN GIZI (JKG), 2026)
The Emergency Department (ED) is a healthcare service area with a high risk of exposure to biological hazards, making the proper use of Personal Protective Equipment (PPE) in accordance with Occupational Health and Safety (OHS) standards essential for healthcare workers. However, non-compliance with PPE use is still frequently observed in primary healthcare facilities. This study aimed to analyze the level of healthcare workers’ compliance with PPE use in the Emergency Department of Lirik Primary Health Care Center, Indragiri Hulu Regency, in 2025. This study was conducted as a residency activity using a descriptive observational design with a risk analysis approach. The study population consisted of all healthcare workers in the Emergency Department of Lirik Primary Health Care Center. The main informant was the ED coordinator, while supporting informants included OHS officers and other healthcare workers. Data were collected through direct observation, in-depth interviews, and document reviews of standard operating procedures (SOPs) and OHS reports. The variables analyzed included the level of PPE compliance and factors contributing to non-compliance. Data analysis employed a fishbone diagram to identify root causes and the Urgency, Seriousness, and Growth (USG) method to determine problem priorities. The results showed that PPE compliance among healthcare workers in the Emergency Department had not yet reached an optimal level. This condition was influenced by behavioral factors, limited availability of OHS educational materials, inadequate supervision, and insufficient availability of PPE at service points. In conclusion, improving PPE compliance requires integrated interventions, including strengthening SOP implementation, providing continuous training, ensuring adequate PPE availability, and conducting routine supervision to support healthcare worker safety and the quality of emergency services.